PENERAPAN NILAI KEISLAMAN MELALUI CARING PEMENUHAN KEBUTUHAN SPIRITUAL SHOLAT PASIEN RAWAT INAP - Noor Azizah; Muhammad Purnomo; Atun Wigati (Jurnal Ilmu Keperawatan dan Kebidanan, 2021)
One of the spiritual needs of Muslims is prayer. Prayer must be done in a state of illness with different procedures according to ability. The purpose of this study was to determine the relationship between the ability of patients and the role of nurses in the application of Islamic Caring for Spiritual Needs. Cross Sectional Sample 50 people. Chi-Square data analysis. The results of the ability of patients with the fulfillment of the spiritual needs of prayer (p value 0.006 0.05), the role of nurses in the application of Islamic values through caring with the fulfillment of the spiritual needs of prayer (p value 0.001 0.05). There is a relationship between the ability of patients and the role of nurses in the application of Islamic values through caring with the fulfillment of the spiritual needs of inpatient prayer.